Carl Brent Swisher collection of research materials relating to Roger B. Taney - Swisher, Carl Brent, 1897-1968.
Chiefly reproductions of correspondence, reports, records, and newspapers gathered by Swisher for a history of Roger B. Taney's tenure as chief justice of the U.S. Supreme Court. Subjects include African Americans, the Bank of the United States, censorship, Civil War, currency, emancipation, Indians, international relations, slavery, slave trade, U.S. Supreme Court, and various court cases. Individuals represented include Jeremiah S. Black, James Buchanan, John Catron, Salmon P. Chase, Nathan Clifford, David Davis, John McLean, Richard Peters, Joseph Story, Martin Van Buren, Daniel Webster, and Gideon Welles. Includes Swisher's correspondence and notes (1958-1962) chiefly relating to administrative matters of the Permanent Committee for the Oliver Wendell Holmes Devise. Swisher's correspondents include Joseph P. Blickensderfer, Lloyd A. Dunlap, and Paul A. Freund.
In part, photocopies and transcripts of originals in various repositories including the Manuscript Division of the Library of Congress, Duke University, Chicago Historical Society, Historical Society of Pennsylvania, Maine Historical Society, Maryland Hall of Records Commission, National Archives and Records Administration, William L. Clements Library of the University of Michigan, and the University of Virginia.
Chicago Historical Society
Duke University
Historical Society of Pennsylvania
Library of Congress Manuscript Division
Maine Historical Society
Keywords: Black, Jeremiah S. -- 1810-1883.; Blickensderfer, Joseph P. -- 1894-1960 -- Correspondence; Buchanan, James, -- 1791-1868.; Catron, John, -- approximately 1786-1865.; Chase, Salmon P. -- 1808-1873.; Clifford, Nathan, -- 1803-1881.; Davis, David, -- 1815-1886.; Dunlap, Lloyd A. -- Correspondence; Freund, Paul A. -- 1908-1992 -- Correspondence; McLean, John, -- 1785-1861.; Peters, Richard, -- 1743-1828.; Story, Joseph, -- 1779-1845.; Taney, Roger Brooke, -- 1777-1864.; Van Buren, Martin, -- 1782-1862.; Webster, Daniel, -- 1782-1852.; Welles, Gideon, -- 1802-1878.; United States. -- Permanent Committee for the Oliver Wendell Holmes Devise; United States. -- Supreme Court; Bank of the United States (1816-1836); African Americans; Banks and banking -- United States; Censorship; Courts -- United States; Indians of North America; International relations; Money; Slavery; Slaves; Slaves -- Emancipation -- United States; Slave trade; United States -- History -- Civil War, 1861-1865.; Historians